Repetitive electrostatic pressurised intraperitoneal aerosol chemotherapy (ePIPAC) with oxaliplatin as a palliative monotherapy for isolated unresectable colorectal peritoneal metastases: protocol of a Dutch, multicentre, open-label, single-arm, phase II study (CRC-PIPAC). Issue 7 (27th July 2019) - Rovers, Koen P; Lurvink, Robin J; Wassenaar, Emma CE; Kootstra, Thomas JM; Scholten, Harm J; Tajzai, Rudaba; Deenen, Maarten J; Nederend, Joost; Lahaye, Max J; Huysentruyt, Clément JR; van 't Erve, Iris; Fijneman, Remond JA; et al.
Abstract : Introduction: Repetitive electrostatic pressurised intraperitoneal aerosol chemotherapy with oxaliplatin (ePIPAC-OX) is offered as a palliative treatment option for patients with isolated unresectable colorectal peritoneal metastases (PM) in several centres worldwide. However, little is known about its feasibility, safety, tolerability, efficacy, costs and pharmacokinetics in this setting. This study aims to explore these parameters in patients with isolated unresectable colorectal PM who receive repetitive ePIPAC-OX as a palliative monotherapy. Methods and analysis: This multicentre, open-label, single-arm, phase II study is performed in two Dutch tertiary referral hospitals for the surgical treatment of colorectal PM. Eligible patients are adults who have histologically or cytologically proven isolated unresectable PM of a colorectal or appendiceal carcinoma, a good performance status, adequate organ functions and no symptoms of gastrointestinal obstruction. Instead of standard palliative treatment, enrolled patients receive laparoscopy-controlled ePIPAC-OX (92 mg/m 2 body surface area (BSA)) with intravenous leucovorin (20 mg/m 2 BSA) and bolus 5-fluorouracil (400 mg/m 2 BSA) every 6 weeks. Four weeks after each procedure, patients undergo clinical, radiological and biochemical evaluation. ePIPAC-OX is repeated until disease progression, after which standard palliative treatment is (re)considered. The primary outcome is the number of patients with major toxicity (grade ≥3 according to the Common Terminology Criteria for Adverse Events v4.0) up to 4 weeks after the last ePIPAC-OX. Secondary outcomes are the environmental safety of ePIPAC-OX, procedure-related characteristics, minor toxicity, postoperative complications, hospital stay, readmissions, quality of life, costs, pharmacokinetics of oxaliplatin, progression-free survival, overall survival, and the radiological, histopathological, cytological, biochemical and macroscopic tumour response. Ethics and dissemination: This study is approved by an ethics committee, the Dutch competent authority and the institutional review boards of both study centres. Results are intended for publication in peer-reviewed medical journals and for presentation to patients, healthcare professionals and other stakeholders. Trial registration number: NCT03246321, Pre-results; ISRCTN89947480, Pre-results; NTR6603, Pre-results; EudraCT: 2017-000927-29, Pre-results.